P106. Anodal tDCS over the left sensorimotor area improves motor symptoms and modulates corticocortical coherence in Parkinson's disease. Issue 8 (August 2018) - Schöllmann, A.; Scholten, M.; Krüger, R.; Plewnia, C.; Weiss, D.
Abstract : Network activity in the beta range is correlated with motor symptoms in Parkinson's disease (PD). Anodal transcranial direct current stimulation (atDCS) over the sensorimotor area modulates cortical excitability and may alleviate motor symptoms in PD. In this study, we aimed to explore the effect of atDCS over the left sensorimotor area on clinical motor outcome, right hand fine motor performance and cortical motor network connectivity. In this double-blind randomized sham-controlled combined EEG and tDCS study, we investigated ten pharmacologically treated idiopathic PD patients after overnight withdrawal of dopaminergic medication and eleven healthy controls during an isometric precision grip task of the right hand before and after stimulation. Participants were studied and crossed-over in two sessions on different days with either 'verum' or 'sham' stimulation of atDCS (20 min; 1 mA; electrodes placed over left 'C3' (anode) and right 'Fp2' (cathode)). Cortical connectivity was expressed as corticocortical imaginary coherence in the high beta band (22–27 Hz) between 'C3' and all other EEG-channels; the topographic distribution was obtained from 25 cortical EEG channels placed according to the 10–20 system. Fine motor performance was expressed as accuracy error during the precision grip task with lower accuracy error indicating higher motor precision. Clinical motor outcome was measured using the UPDRS III motor score. PD patients with 'verum' stimulation showed an increase of corticocortical imaginary coherence in the high beta band from 'C3' to the right motor area 30 min after stimulation. This was paralleled by a significant decrease in the UPDRS III motor score. There was no similar modulation in PD 'sham' stimulation and in healthy controls in both 'verum' and 'sham' conditions. However, interestingly, HC showed beta band coupling prior to stimulation directed from 'C3' to the right hemisphere. Both groups showed no significant change regarding the accuracy error after stimulation. AtDCS of 'C3' entrains beta band coupling between 'C3' and the right sensorimotor area with 'C3' leading right hemispheric beta band oscillations in the temporal domain. We speculate that this could represent a mechanism to tone down inhibitory influences of the right hemisphere ipsilateral to the right hand, given that increased beta synchrony is associated with increasing motor inhibition in previous studies.